2013
DOI: 10.1002/uog.12372
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of chromosomal abnormalities in fetuses with abnormal cardiac ultrasound findings: evaluation of chromosomal microarray‐based analysis

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 48 publications
5
59
2
1
Order By: Relevance
“…It is known that abnormal prenatal ultrasound scans are associated with a high rate of chromosomal abnormality,26 and in our study, an abnormal ultrasound scan was one of the most reliable indications for identifying an SCA. This is consistent with other studies that have demonstrated high rates of chromosomal abnormalities in pregnancies with abnormal ultrasound scans27 and may be a sign of technological improvements in medical imaging. Improvements in ultrasound scanning may also be reflected in the termination rates found in this study; of those pregnancies that resulted in termination, 83% had an abnormal antenatal ultrasound scan.…”
Section: Discussionsupporting
confidence: 91%
“…It is known that abnormal prenatal ultrasound scans are associated with a high rate of chromosomal abnormality,26 and in our study, an abnormal ultrasound scan was one of the most reliable indications for identifying an SCA. This is consistent with other studies that have demonstrated high rates of chromosomal abnormalities in pregnancies with abnormal ultrasound scans27 and may be a sign of technological improvements in medical imaging. Improvements in ultrasound scanning may also be reflected in the termination rates found in this study; of those pregnancies that resulted in termination, 83% had an abnormal antenatal ultrasound scan.…”
Section: Discussionsupporting
confidence: 91%
“…The detection rate for potentially causal CNVs was 25% (with 1 Mb resolution). In 2013, Mademont-Soler et al [22] reported that 6.4% of fetuses with CHDs had 22q11.2 deletion syndrome. However, when this microdeletion syndrome and abnormal karyotype were excluded, the detection rate of pathogenic CNVs was 2.0% in fetuses with a CHD and no detectable VOUS.…”
Section: Discussionmentioning
confidence: 99%
“…• Over 35 years of maternal age [4] • Identified or assumed family history of genetic disease [5] • Ethnicity at high risk for genetic disease [6,7,8] • Multiple pregnancy losses [9] • Teratogen [10] • Alterations of standard ultrasound findings [11,12] • Unusual maternal serum screen results [13,14].…”
Section: Indications Of Prenatal Diagnosismentioning
confidence: 99%